2021
DOI: 10.1123/jpah.2021-0077
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Meeting the Physical Activity Guidelines: Muscle-Strengthening Alone and Combined With Aerobic Activity, United States, 1998–2018

Abstract: Background: The National Health Interview Survey is unique among US federal surveillance systems with over 20 years of consistent assessment of muscle-strengthening and aerobic activity. The authors examined trends in the prevalence of US adults who met the muscle-strengthening (2 or more days per week) and the combined muscle-strengthening and aerobic physical activity (at least 150 min/wk of moderate-intensity equivalent activity) guidelines from 1998 to 2018. Methods: The 1998–2018 National Health Interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 8 publications
4
61
0
Order By: Relevance
“…This was observed in this study with fluid volume [2,662 ± 1,444 ml; t (487) , 2.660; p = 0.008] and water intake [1,796 ± 1,156 ml; t (487) , 3.679; p < 0.001] greater in those who completed >150 min of moderate–vigorous physical activities per week. Observational trends in those who meet the Physical Activity Guidelines for Americans show a 9.6% increase from 1998 to the latest report released by the CDC in 2018 (Hyde et al, 2021 ). Increases in total FI and shifts in fluid preference to water intake may be related to an increase in physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…This was observed in this study with fluid volume [2,662 ± 1,444 ml; t (487) , 2.660; p = 0.008] and water intake [1,796 ± 1,156 ml; t (487) , 3.679; p < 0.001] greater in those who completed >150 min of moderate–vigorous physical activities per week. Observational trends in those who meet the Physical Activity Guidelines for Americans show a 9.6% increase from 1998 to the latest report released by the CDC in 2018 (Hyde et al, 2021 ). Increases in total FI and shifts in fluid preference to water intake may be related to an increase in physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why there was no difference in the number of days of strength training in the depressed and non-depressed groups is not that strength training has no effect on depression, but rather that the exercise rate itself is low in the elderly. In this regard, in order to increase the participation rate in muscle-strengthening activities in the future physical activity promotion strategy, it was suggested that adults over 65 years of age should be selected as a priority group [24].…”
Section: Discussionmentioning
confidence: 99%
“…22,24 Meanwhile, more adults aged 18−44 years are meeting the combined aerobic and muscle-strengthening physical activity guidelines in leisure time, but the 2018 prevalence remained below 25%. 25 The impact of these trends on military preparedness is unknown. The most recently published manuscript on the topic used 2007−2008 data.…”
Section: Introductionmentioning
confidence: 99%